Agricultural Waste–Derived Biochar for Antibiotics Removal in Aqueous Environment: A Comprehensive Outlook - Varalakshmi Varatharajan; Karthik V.; Selvakumar Periyasamy (Journal of Chemistry)
Increased antibiotic consumption and inadequate management procedures expose the environment to antibiotics, leading to significant antibiotic pollution and emerging antibiotic-resistant microbes. Biochar form agricultural waste can efficiently remove antibiotics from aquatic environments and is a renewable and cost-effective adsorbent. Biochar-producing methods from different agricultural residues, the physicochemical characteristics, and the adsorption effectiveness of biochar are discussed. Surface modification of biochar provides a variety of new interactions between the biochar and antibiotics. The key elements influencing antibiotic adsorption on biochar, including surface chemistry, pyrolysis conditions, and environmental variables, were discussed in detail. This review focuses specifically on the functional modification of the biochar, the mechanism involved in antibiotic adsorption, and the scalability of this process. The difficulties with biochar regeneration, environmental risks, and industrial viability are also addressed. The findings highlighted that the existing adsorption approaches for antibiotic removal need adsorbent with prolonged stability, process optimization, and cost-effective regenerative techniques. This review gives a broad overview of antibiotic removal using biochar and aids the decision-makers in developing environmentally friendly water treatment systems.